The Ultimate Solution of any JOINT âPAIN (Coservative) JOINT-CURE Harbal for Osteoarthitis, Rheumatoid Arthritis, Backache due to Facet Arthritis, Spondilytis and Other Joint Pain - Patel, Shahil (Journal of Medical Biomedical and Applied Sciences, 2017)
Abstract: Aim:Why we get PAIN???Do we exercise every day?Do we have proper diet, water, air?How many of us are using PAIN KILLER MEDICINE daily?Without knowing the fact of PAIN Killer safety.....To find the effectiveness, Randomise Clinical trials with the Use of the JOINT -CURE herble"Churna" as an alternative treatment to any invasion in joints for the Pain relief ofOsteoarthritis, Rheumatoid arthritis, Facet Arthritis and / or any kind of Joint Pain.